Optimization of a Layout for Public Toilets Based on Evaluation of Accessibility Through the Gaussian Two-Step Floating Catchment Area Approach - Quanli Xu; Youyou Li; Jiali Niu; You Li; Huishan Wu (ISPRS International Journal of Geo-Information, 2025)
Urban public toilets are essential for improving urban and rural living environments. Traditional evaluations have relied on statistical indicators such as total numbers and network coverage, but have overlooked population demand, limiting their ability to reflect actual service levels and optimize spatial allocation. This study assesses the public toilet service capacity according to spatial accessibility and offers insights into layout optimization. The main urban area of Kunming was considered as the case study. First, the Gaussian two-step floating catchment area (G2SFCA) method was used to calculate public toilet accessibility. The service level of public toilets at the community scale was assessed based on the calculation results. Finally, recommendations for the optimization of the spatial layout of public toilet provision are proposed based on the evaluation findings. Results indicate that (1) 57 communities lacked access to public toilets within a 5 min walk, while only two lacked access within 20 min; all communities had access within 30 min; (2) increasing stalls in old public toilets by 50% would meet the policy requirements for most residents; (3) transportation accessibility has a significant impact on residents’ convenience in accessing public toilets. Areas with lower transportation connectivity tend to have poorer toilet accessibility. The construction of new public toilets near road networks can effectively enhance overall restroom convenience for residents in the study area. By integrating public toilet accessibility with resident restroom demand, this study proposes targeted strategies for optimizing the spatial layout of urban public toilets, offering valuable insights and feasible solutions for improving the scientific and rational allocation of urban public resources.